2021
DOI: 10.3390/nu13072184
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antiplatelets: A New Perspective on the Health Benefits of the Water-Soluble Tomato Concentrate Fruitflow®

Abstract: Our understanding of platelet functionality has undergone a sea change in the last decade. No longer are platelets viewed simply as regulators of haemostasis; they are now acknowledged to be pivotal in coordinating the inflammatory and immune responses. This expanded role for platelets brings new opportunities for controlling a range of health conditions, targeting platelet activation and their interactions with other vascular cells. Antiplatelet drugs may be of wider utility than ever expected but often cause… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 81 publications
(109 reference statements)
0
14
0
Order By: Relevance
“…Previous acute clinical trials have shown that a single dose of WTE inhibited platelet aggregation and activation after 3 or 7 h in the British adults ( 14 , 15 ). Recent reviews have shown that WTE was a potential therapeutic agent for inhibiting platelet function and might circumvent the negative drawbacks of using aspirin, clopidogrel, or ticagrelor ( 16 , 17 ). However, the effect and safety of 4-week administration of WTE remains unclear, and there is no study exploring the effect of WTE on platelet function in Chinese middle-aged and older individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Previous acute clinical trials have shown that a single dose of WTE inhibited platelet aggregation and activation after 3 or 7 h in the British adults ( 14 , 15 ). Recent reviews have shown that WTE was a potential therapeutic agent for inhibiting platelet function and might circumvent the negative drawbacks of using aspirin, clopidogrel, or ticagrelor ( 16 , 17 ). However, the effect and safety of 4-week administration of WTE remains unclear, and there is no study exploring the effect of WTE on platelet function in Chinese middle-aged and older individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Krasińska et al ( 20 ) indicated a significant hypotensive effect for 213 mg/day of standardized tomato extract administered for 4 weeks in 32 patients with at least high cardiovascular risk based on the European Society of Cardiology (ESC) and the European Society of Hypertension (ESH) in 2013 ( 55 ). More recently, O'Kennedy et al ( 29 ) found that daily supplementation with Fruitflow® tomato extract reduces platelet aggregation in humans in response to different cofactors, molecules, and enzymes (ADP, collagen, arachidonic acid, and thrombin) involved in platelet activation. Furthermore, the authors suggested a possible beneficial effect of this tomato extract on some cardiovascular risk factors after intense physical activity that promotes a strong inflammatory response and platelet activation.…”
Section: Scientific Evidence On the Relationship Between Tomato And L...mentioning
confidence: 99%
“…Other authors have reported a decrease in various cardiovascular risk factors after supplementation with tomato extracts and their derivatives. McEwen (51) (29) found that daily supplementation with Fruitflow R tomato extract reduces platelet aggregation in humans in response to different cofactors, molecules, and enzymes (ADP, collagen, arachidonic acid, and thrombin) involved in platelet activation. Furthermore, the authors suggested a possible beneficial effect of this tomato extract on some cardiovascular risk factors after intense physical activity that promotes a strong inflammatory response and platelet activation.…”
Section: Scientific Evidence On the Relationship Between Tomato And L...mentioning
confidence: 99%
“…Aspirin and receptor antagonists of the P2Y12 and GPIIb-IIIa integrins influence platelet-vessel wall interaction. Aspirin has other pharmacological effects besides inhibiting platelet aggregation (O'Kennedy et al, 2021). Inhibitors of platelet synthesis of TXA 2 may also affect the cross-talk between platelets and vascular endothelium as it influences vessel wall constriction and vascular cell proliferation (Zucker et al, 1997).…”
Section: Effects Of Antiplatelet Compounds On Plateletvessel Wall Int...mentioning
confidence: 99%